2021
DOI: 10.2196/25462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Implementation and Effectiveness of Community-Based Brain-Computer Interface Cognitive Group Training in Healthy Community-Dwelling Older Adults: Randomized Controlled Implementation Trial

Abstract: Background Cognitive training can improve cognition in healthy older adults. Objective The objectives are to evaluate the implementation of community-based computerized cognitive training (CCT) and its effectiveness on cognition, gait, and balance in healthy older adults. Methods A single-blind randomized controlled trial with baseline and follow-up assessments was conducted at two community centers in Singapore. Healthy community-dwelling ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“… 13 More recent studies have found significant differences, when compared to a control group (CG), in cognitive skills such as driving, inhibition tasks, processing speed, 14 inhibition, and working memory. 15 In contrast, one study 16 found an improvement in gait among the CG and a significant deterioration in list recognition among the experimental group. However, various theoretical, methodological, and design limitations of the included studies could restrict the scope of these results.…”
Section: Introductionmentioning
confidence: 87%
“… 13 More recent studies have found significant differences, when compared to a control group (CG), in cognitive skills such as driving, inhibition tasks, processing speed, 14 inhibition, and working memory. 15 In contrast, one study 16 found an improvement in gait among the CG and a significant deterioration in list recognition among the experimental group. However, various theoretical, methodological, and design limitations of the included studies could restrict the scope of these results.…”
Section: Introductionmentioning
confidence: 87%